Organizational Innovation, R&D and Product Innovation: Firm-Level Evidence from ASEAN Countries - Nguyen-Van, Dung; Chang, Chia-Hua (Journal of Entrepreneurship, Business and Economics, 2020)
The study explores the direct effects of organizational innovation and R&D (research and development) and the complementary effect of these two factors on the likelihood of innovation at a higher degree of radicalness in ASEAN. This research focus is important as little is known about the role of organizational innovation and the combination of this type of innovation with R&D for product innovation efforts. The study uses cross-sectional data from the World Bank’s Enterprise Survey in 2015-2016 and a generalized ordered logit model to address the common limitation of the standard ordered logit model in estimation. The findings show that both organizational innovation and R&D have significantly positive effects on the possibility of innovation at a higher degree of radicalness. The positive complementary effect of organizational innovation and R&D is also supported. The practical implications emphasize that ASEAN firms should devote more resources to organizational innovation and R&D to boost their product innovation performance. Research paper Keywords: ASEAN; Generalized ordered logit model; Organizational innovation; Product innovation; R&D Reference to this paper should be made as follows: Nguyen-Van, D., & Chang, C. (2020). Organizational Innovation, R&D and Product Innovation: Firm-Level Evidence from ASEAN Countries, Journal of Entrepreneurship, Business and Economics , 8 (1), 54–76.